The Role of Electronic Journalism in Supporting National Identity among Iraqi Youth - Hamza Khaled Mutshar, Rese. (lark, 2025)
The research examines the impact of electronic journalism in strengthening national identity among Iraqi youth, while highlighting the challenges and opportunities provided by this modern media. The research discusses the concept of national identity and its importance in the Iraqi context, especially in light of the ongoing political and social changes. It also reviews the various forms of electronic journalism, such as blogs, news websites, and social media, and their role in enhancing young people’s sense of national belonging. The research addresses how these platforms contribute to disseminating information, exchanging opinions, and promoting dialogue between different social groups. The results show that electronic journalism plays an important role in shaping national identity by providing content that reflects Iraqi values ​​and culture. It also contributes to increasing national awareness among young people, which enhances their ability to confront external pressures and contributes to building a cohesive and strong civil society.